Physiological Demands of Trampolining at Different Intensities. Issue 1 (2nd January 2020) - Draper, Nick; Clement, Tane; Alexander, Keith
ABSTRACT: Purpose : The aim of this study was to examine the physiological demands of trampolining, in comparison with treadmill running, using a larger sample size and a wider range of physiological measures, than had been reported in the previous research. Method : Twenty-three healthy adults completed three, three-minute exercise bouts on both a trampoline and treadmill at different intensities. Heart rate (HR), oxygen consumption ( V ˙ O 2 ), energy expenditure (EE) and blood lactate (BL) were collected for each bout. Results : Results of a two-way repeated measures MANOVA indicated that there was a significant difference between the modalities ( F 6, 86 = 9.3, p <.0005, n 2 p a r t i a l = 0.39). A follow up two-way repeated measures ANOVA then identified that significant differences existed between the modalities for each of the variables; V ˙ O 2 ( F 2, 44 = 159, p <.0005, n 2 p a r t i a l = 0.88), EE (= 136, p <.0005, n 2 p a r t i a l = 0.86) and BL ( F 2, 44 = 171, p <.0005, n 2 p a r t i a l = 0.89). Subsequent post hoc testing found V ˙ O 2 to differ significantly between the medium intensities ( p =.01 d =0.6). EE to differ significantly for the medium ( p =.003, d =−0.7) and high intensities ( p =.02, d =−0.5). BL to differ significantly for the low ( p =.04, d =0.4), medium ( p =.03, d =0.5) and high ( p =.001 d =1.4) intensities. Conclusions : The results from our study indicated that while significant differences do occur between running and trampolining for a given intensity, the trendline associated with each of the variables is similar. Therefore, monitoring the intensity of the session based the percentage of the participant's maximum heart rate, which is commonly used in running, may also be applied to trampolining.